CFO Attributes and Corporate Risk Management : Evidence from Top 100 Firms in Malaysia - Azra, Tilai; Josephine Yau, Tan Hwang; Audrey, Liwan (UiTM Press, 2023)
The research aims to investigate the relationship between Chief Financial Officer (CFO) attributes and corporate risk management of the Top 100 Firms in Malaysia. A sample of 8 years from 2012 to 2019 with 704 observations excluding financial firms is used. Corporate risk management is measured by two proxies: hedging decisions and the usage of financial derivatives. The independent variables are CFO attributes (age, gender, education level, professional qualification, tenure, and nationality). This study is controlled with leverage, firm size, profitability, cost of financial distress, and capital expenditure. Panel logistic regression is conducted to analyse the relationship between the CFO attributes and hedging decisions. Based on the main findings, CFO age, gender, education level, and nationality significantly impact corporate risk management. In contrast, CFO professional qualification and tenure do not impact corporate risk management in this study. This research makes a valuable contribution to policymakers by enhancing their understanding of risk management regulations. The study provides crucial insights for Malaysian firms, helping them make informed decisions regarding capital raising, investments, and risk management. Moreover, the findings empower CFOs with valuable knowledge about the relevance of their attributes in effectively managing corporate risk through hedging activities.